A heat-resistant tensile molybdenum-copper alloy material and a preparation method thereof
Patent Information
- Application Number
- CN202611134476.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]目前钼铜合金材料主要通过粉末冶金的方式进行制备,使得制备得到的钼铜合金材料致密性并不好,进而导致其存在力学性能欠佳的缺陷,这在一定程度上限制了其在严苛工况的长期使用
1、镍可以起到活化钼、铜合金烧结的作用,极大提高合金材料的致密性,进而提高钼铜合金的抗拉强度,但合金混合料中镍粉的加入量不易过多,过多会导致钼铜合金材料脆性大幅增加,反而使得抗拉性能变差,因此镍粉的加入量控制在0.4~0.8wt%为宜;同时为了降低钼铜合金材料的脆性,本发明在合金混合料中加入了碳化钛晶须,其作为核心增强材料均匀分散在钼铜合金材料中,可显著提高材料韧性,同时其可阻碍位错滑移,使得钼铜合金的抗拉强度发生显著增强。稀土金属粉则起到净化晶界的作用,辅助碳化钛晶须提高合金的抗拉性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy technology, specifically to a heat-resistant and tensile-strength molybdenum-copper alloy material and its preparation method. Background Technology
[0002] Molybdenum-copper alloy is a high-performance metal-based composite material that combines the high melting point and low coefficient of thermal expansion of molybdenum with the high thermal conductivity of copper. It is widely used in semiconductor packaging, high-temperature devices, and aerospace, and is one of the core materials for the manufacture of high-end equipment.
[0003] Currently, molybdenum-copper alloys are mainly prepared using powder metallurgy, which results in poor density and consequently, suboptimal mechanical properties. This limits their long-term use under harsh operating conditions. Existing techniques often involve adding nickel to molybdenum-copper alloys to activate sintering and improve density. However, even a slight excess of nickel significantly increases the brittleness of the alloy, leading to a marked decrease in tensile strength and a noticeable reduction in heat resistance.
[0004] Therefore, in order to enhance the applicability of molybdenum-copper alloy materials, this invention provides a heat-resistant and tensile-strength molybdenum-copper alloy material and its preparation method, which is of great significance. Summary of the Invention
[0005] The purpose of this invention is to provide a heat-resistant and tensile-strength molybdenum-copper alloy material and its preparation method, so as to solve the related technical problems existing in the prior art.
[0006] To achieve the above objectives, the first aspect of the present invention provides the following specific technical solution: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Add molybdenum powder, copper powder, nickel powder, and rare earth metal powder into a ball mill and ball mill; then add titanium carbide whiskers and mix to obtain an alloy mixture. S2: The alloy mixture is dried, cold isostatically pressed, sintered, heat-treated, and rolled to obtain a molybdenum-copper alloy material. S3: Molybdenum-copper alloy material is laser clad and nitrided to obtain heat-resistant and tensile-strength molybdenum-copper alloy material.
[0007] Furthermore, the parameters for the ball milling are as follows: argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as the grinding balls; the ball-to-material ratio is (5~20):1, the ball milling speed is 200~400 r / min, and the ball milling time is 6~10 h.
[0008] Furthermore, the mixing process involves mixing at a stirring speed of 40-60 r / min for 30-60 min; the mixing speed is reduced to avoid damaging the titanium carbide whiskers.
[0009] Furthermore, the alloy mixture comprises the following raw material components by mass percentage: 15-20 wt% copper powder, 0.4-0.8 wt% nickel powder, 0.1-0.5 wt% rare earth metal powder, 1-2 wt% titanium carbide whiskers, and the remainder being molybdenum powder.
[0010] Furthermore, the drying process involves vacuum drying at 75-85°C for 2-4 hours.
[0011] Furthermore, the cold isostatic pressing is performed by holding the pressure at 180~220MPa for 10~30min.
[0012] Furthermore, the sintering is performed by discharge plasma sintering at 1000~1200℃ for 10~30 minutes under argon protection.
[0013] Furthermore, the heat treatment is performed by holding at 600~800℃ for 1~3 hours under argon protection.
[0014] Furthermore, the rolling deformation is as follows: rolling at 900~1000℃ and a rolling speed of 0.2~1m / s until the total deformation is 50~80%.
[0015] Further, before adding the titanium carbide whiskers, a dispersion pretreatment is performed on them. The specific method is as follows: (1) Add the titanate coupling agent to an 80~90wt% ethanol aqueous solution, adjust the pH to 4.8~5.2, stir and mix for 30~60min to obtain the coupling agent hydrolysate; (2) Add the titanium carbide whiskers to the coupling agent hydrolysate, stir and mix for 30~60min, filter, wash, and dry; then add them to anhydrous ethanol, ultrasonically disperse for 10~20min to complete the dispersion pretreatment.
[0016] Furthermore, the ratio of the titanate coupling agent to the ethanol aqueous solution is (0.02~0.06) g: 1 mL.
[0017] Furthermore, the ratio of the titanium carbide whiskers, coupling agent hydrolysate, and anhydrous ethanol is (1~2)g:5mL:5mL.
[0018] Pretreatment of titanium carbide whiskers promotes their dispersion and enhances their reinforcing effect.
[0019] Furthermore, the cladding material used in the laser cladding includes the following raw material components: by mass percentage, 1-3 wt% titanium powder, 10-15 wt% chromium powder, 2-4 wt% nickel powder, 2-3 wt% titanium carbide whiskers, 2-5 wt% tungsten powder, 0.1-0.5 wt% rare earth metal powder, and the remainder is molybdenum powder.
[0020] Furthermore, the parameters of the laser cladding are as follows: argon gas is used as the protective gas, the laser power is 800~1000W, the scanning speed is 3~5mm / s, the spot diameter is 2~4mm, and the cladding thickness is 0.5~1mm.
[0021] Furthermore, the parameters for nitriding are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:(1~2), a gas flow rate of 0.5~1L / min, a working voltage of 600~800V, a nitriding temperature of 500~600℃, a nitriding pressure of 0.2~0.4MPa, and a nitriding depth of 0.1~0.2mm.
[0022] A second aspect of the present invention provides a heat-resistant and tensile-strength molybdenum-copper alloy material prepared by the above-described preparation method.
[0023] Compared with the prior art, the beneficial effects of the present invention are: 1. Nickel can activate the sintering of molybdenum-copper alloys, greatly improving the density of the alloy material and thus increasing the tensile strength of the molybdenum-copper alloy. However, the amount of nickel powder added to the alloy mixture should not be excessive, as too much will lead to a significant increase in the brittleness of the molybdenum-copper alloy, resulting in a deterioration in tensile properties. Therefore, the amount of nickel powder added should be controlled at 0.4~0.8wt%. Simultaneously, to reduce the brittleness of the molybdenum-copper alloy, this invention adds titanium carbide whiskers to the alloy mixture. These whiskers, as a core reinforcing material, are uniformly dispersed in the molybdenum-copper alloy, significantly improving the material's toughness. They also hinder dislocation slip, resulting in a significant increase in the tensile strength of the molybdenum-copper alloy. Rare earth metal powder acts to purify grain boundaries, assisting the titanium carbide whiskers in improving the tensile properties of the alloy.
[0024] 2. This invention further employs a mixture of titanium powder, chromium powder, nickel powder, titanium carbide whiskers, tungsten powder, rare earth metal powder, and molybdenum powder to prepare a cladding material, which is then used to laser-clad a layer onto the surface of a molybdenum-copper alloy. The presence of titanium carbide whiskers further enhances the density of the cladding layer, thus improving the tensile strength of the molybdenum-copper alloy. Additionally, tungsten powder and titanium powder are specifically added to the cladding material; both can form reinforcing agents during subsequent nitriding, significantly enhancing the heat resistance of the alloy. Chromium significantly improves the interfacial bonding between the cladding layer and the molybdenum-copper alloy.
[0025] 3. In this invention, the laser cladding layer is further subjected to nitriding treatment. Nitriding allows the relevant elements in the cladding layer to form nitrides with nitrogen, thereby forming a nitride layer with excellent performance. Under the synergistic effect of nitriding treatment and laser cladding, the mechanical properties and heat resistance of the molybdenum-copper alloy material are further improved.
[0026] 4. The reason for choosing to perform laser cladding first in this invention is that if nitriding is directly applied to the molybdenum-copper alloy material, copper cannot participate in the nitriding process, resulting in poor nitriding performance. Therefore, this invention first performs laser cladding, creating a tightly bonded cladding layer on the molybdenum-copper alloy substrate, followed by nitriding. Through the synergistic effect of laser cladding and nitriding, a comprehensive improvement in the tensile strength and heat resistance of the molybdenum-copper alloy material is achieved.
[0027] In summary, this invention has successfully prepared a heat-resistant and tensile molybdenum-copper alloy material with high tensile strength and high heat resistance, which is of great significance. Detailed Implementation
[0028] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. It should be understood that the embodiments described herein are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort should fall within the protection scope of the present invention; unless otherwise specified, the related raw materials are all conventional settings.
[0029] It should be noted that the following proportions are by weight. There are no special restrictions on the purchasers of any of the raw materials involved in this invention. Exemplary examples include: the particle size of molybdenum powder is 4μm; the particle size of copper powder is 6μm; the particle size of nickel powder is 4μm; the particle size of titanium powder is 6μm; the particle size of cerium powder is 6μm; the diameter of titanium carbide whiskers is 1μm and the aspect ratio is 15; the particle size of chromium powder is 6μm; the particle size of tungsten powder is 4μm; the titanate coupling agent is model 201; and the dimensions of the molybdenum-copper alloy material are: length 200mm × width 10mm × thickness 5mm.
[0030] Preparatory steps: The titanium carbide whiskers were dispersed and pretreated. The specific method was as follows: (1) Add titanate coupling agent 201 to 85wt% ethanol aqueous solution, adjust the pH to 5.0, stir and mix for 40min to obtain coupling agent hydrolysate, wherein the ratio of titanate coupling agent 201 to ethanol aqueous solution was 0.04:1mL; (2) Add titanium carbide whiskers to coupling agent hydrolysate, stir and mix for 45min, filter, wash, and dry; then add to anhydrous ethanol, ultrasonically disperse for 15min to complete the dispersion pretreatment, wherein the ratio of titanium carbide whiskers, coupling agent hydrolysate, and anhydrous ethanol was 1.5g:5mL:5mL.
[0031] Example 1: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material, comprising the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 17.5 wt% copper powder, 0.6 wt% nickel powder, 0.3 wt% rare earth metal powder, 1.5 wt% titanium carbide whiskers, and the remainder being molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Laser cladding, nitriding: S31: Molybdenum powder, titanium powder, chromium powder, nickel powder, and tungsten powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain the cladding material. The cladding material comprises the following raw material components by mass percentage: 2 wt% titanium powder, 12.5 wt% chromium powder, 3 wt% nickel powder, 2.5 wt% titanium carbide whiskers, 3.5 wt% tungsten powder, 0.3 wt% rare earth metal powder, and the remainder is molybdenum powder; S32: Laser cladding is performed on the surface of molybdenum-copper alloy material using cladding material to form a cladding layer; the parameters of laser cladding are: argon as protective gas, laser power of 900W, scanning speed of 4mm / s, spot diameter of 3mm, and cladding thickness of 0.8mm. S33: After laser cladding, the cladding layer is finely ground and polished to a roughness of 0.5μm, and then nitrided to obtain a heat-resistant and tensile-strength molybdenum-copper alloy material. The nitriding parameters are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:1.5, a gas flow rate of 0.75L / min, a working voltage of 700V, a nitriding temperature of 550℃, a nitriding pressure of 0.3MPa, and a nitriding depth of 0.15mm.
[0032] Example 2: Example 2 is based on Example 1, but with adjustments to the following: the amount of raw material components in the alloy mixture and cladding material, while keeping other processes unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 15 wt% copper powder, 0.4 wt% nickel powder, 0.1 wt% rare earth metal powder, 1 wt% titanium carbide whiskers, and the remainder is molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Laser cladding, nitriding: S31: Molybdenum powder, titanium powder, chromium powder, nickel powder, and tungsten powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain the cladding material. The cladding material comprises the following raw material components by mass percentage: 1 wt% titanium powder, 10 wt% chromium powder, 2 wt% nickel powder, 2 wt% titanium carbide whiskers, 2 wt% tungsten powder, 0.1 wt% rare earth metal powder, and the remainder is molybdenum powder. S32: Laser cladding is performed on the surface of molybdenum-copper alloy material using cladding material to form a cladding layer; the parameters of laser cladding are: argon as protective gas, laser power of 900W, scanning speed of 4mm / s, spot diameter of 3mm, and cladding thickness of 0.8mm. S33: After laser cladding, the cladding layer is finely ground and polished to a roughness of 0.5μm, and then nitrided to obtain a heat-resistant and tensile-strength molybdenum-copper alloy material. The nitriding parameters are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:1.5, a gas flow rate of 0.75L / min, a working voltage of 700V, a nitriding temperature of 550℃, a nitriding pressure of 0.3MPa, and a nitriding depth of 0.15mm.
[0033] Example 3: Example 3 is based on Example 1, but with adjustments to the following: the amount of raw material components in the alloy mixture and cladding material, while keeping other processes unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 20 wt% copper powder, 0.8 wt% nickel powder, 0.5 wt% rare earth metal powder, 2 wt% titanium carbide whiskers, and the remainder is molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Laser cladding, nitriding: S31: Molybdenum powder, titanium powder, chromium powder, nickel powder, and tungsten powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain the cladding material. The cladding material comprises the following raw material components by mass percentage: 3 wt% titanium powder, 15 wt% chromium powder, 4 wt% nickel powder, 3 wt% titanium carbide whiskers, 5 wt% tungsten powder, 0.5 wt% rare earth metal powder, and the remainder is molybdenum powder. S32: Laser cladding is performed on the surface of molybdenum-copper alloy material using cladding material to form a cladding layer; the parameters of laser cladding are: argon as protective gas, laser power of 900W, scanning speed of 4mm / s, spot diameter of 3mm, and cladding thickness of 0.8mm. S33: After laser cladding, the cladding layer is finely ground and polished to a roughness of 0.5μm, and then nitrided to obtain a heat-resistant and tensile-strength molybdenum-copper alloy material. The nitriding parameters are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:1.5, a gas flow rate of 0.75L / min, a working voltage of 700V, a nitriding temperature of 550℃, a nitriding pressure of 0.3MPa, and a nitriding depth of 0.15mm.
[0034] The following comparative experiments are based on Example 1, specifically Comparative Examples 1 to 6: Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustment: titanium carbide whiskers are not added to the alloy mixture, while other processes remain unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added into a ball mill. Argon is used as a protective gas, anhydrous ethanol is used as a dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min to obtain an alloy mixture. The alloy mixture comprises the following raw material components: by mass percentage, 17.5 wt% copper powder, 0.6 wt% nickel powder, 0.3 wt% rare earth metal powder, and the remainder is molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Laser cladding, nitriding: S31: Molybdenum powder, titanium powder, chromium powder, nickel powder, and tungsten powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain the cladding material. The cladding material comprises the following raw material components by mass percentage: 2 wt% titanium powder, 12.5 wt% chromium powder, 3 wt% nickel powder, 2.5 wt% titanium carbide whiskers, 3.5 wt% tungsten powder, 0.3 wt% rare earth metal powder, and the remainder is molybdenum powder; S32: Laser cladding is performed on the surface of molybdenum-copper alloy material using cladding material to form a cladding layer; the parameters of laser cladding are: argon as protective gas, laser power of 900W, scanning speed of 4mm / s, spot diameter of 3mm, and cladding thickness of 0.8mm. S33: After laser cladding, the cladding layer is finely ground and polished to a roughness of 0.5μm, and then nitrided to obtain a heat-resistant and tensile-strength molybdenum-copper alloy material. The nitriding parameters are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:1.5, a gas flow rate of 0.75L / min, a working voltage of 700V, a nitriding temperature of 550℃, a nitriding pressure of 0.3MPa, and a nitriding depth of 0.15mm.
[0035] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustment: titanium carbide whiskers are not added to the cladding material, while other processes remain unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 17.5 wt% copper powder, 0.6 wt% nickel powder, 0.3 wt% rare earth metal powder, 1.5 wt% titanium carbide whiskers, and the remainder being molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Laser cladding, nitriding: S31: Molybdenum powder, titanium powder, chromium powder, nickel powder, and tungsten powder are added into a ball mill, with argon as the protective gas, anhydrous ethanol as the dispersion medium, and zirconia balls as the grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min to obtain the cladding material. The cladding material comprises the following raw material components by mass percentage: 2 wt% titanium powder, 12.5 wt% chromium powder, 3 wt% nickel powder, 3.5 wt% tungsten powder, 0.3 wt% rare earth metal powder, and the remainder is molybdenum powder; S32: Laser cladding is performed on the surface of molybdenum-copper alloy material using cladding material to form a cladding layer; the parameters of laser cladding are: argon as protective gas, laser power of 900W, scanning speed of 4mm / s, spot diameter of 3mm, and cladding thickness of 0.8mm. S33: After laser cladding, the cladding layer is finely ground and polished to a roughness of 0.5μm, and then nitrided to obtain a heat-resistant and tensile-strength molybdenum-copper alloy material. The nitriding parameters are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:1.5, a gas flow rate of 0.75L / min, a working voltage of 700V, a nitriding temperature of 550℃, a nitriding pressure of 0.3MPa, and a nitriding depth of 0.15mm.
[0036] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustment: laser cladding is not performed, while other processes remain unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 17.5 wt% copper powder, 0.6 wt% nickel powder, 0.3 wt% rare earth metal powder, 1.5 wt% titanium carbide whiskers, and the remainder being molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Nitriding treatment is performed on molybdenum-copper alloy material to obtain heat-resistant and tensile-strength molybdenum-copper alloy material; the nitriding parameters are as follows: a mixture of nitrogen and ammonia gas is used as the nitriding medium, the volume ratio of the two is 1:1.5, the gas flow rate is 0.75L / min, the working voltage is 700V, the nitriding temperature is 550℃, the nitriding pressure is 0.3MPa, and the nitriding depth is 0.15mm.
[0037] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustment: nitriding treatment is not performed, while other processes remain unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 17.5 wt% copper powder, 0.6 wt% nickel powder, 0.3 wt% rare earth metal powder, 1.5 wt% titanium carbide whiskers, and the remainder being molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Laser cladding: S31: Molybdenum powder, titanium powder, chromium powder, nickel powder, and tungsten powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain the cladding material. The cladding material comprises the following raw material components by mass percentage: 2 wt% titanium powder, 12.5 wt% chromium powder, 3 wt% nickel powder, 2.5 wt% titanium carbide whiskers, 3.5 wt% tungsten powder, 0.3 wt% rare earth metal powder, and the remainder is molybdenum powder; S32: Laser cladding is performed on the surface of molybdenum-copper alloy material using cladding material to form a cladding layer, resulting in heat-resistant and tensile-strength molybdenum-copper alloy material; the parameters of laser cladding are: argon as the protective gas, laser power of 900W, scanning speed of 4mm / s, spot diameter of 3mm, and cladding thickness of 0.8mm. Comparative Example 5: Comparative Example 5 is based on Example 1, with the following adjustments: laser cladding and nitriding are omitted, while other processes remain unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers that have undergone dispersion pretreatment are added to the mixture, and the mixture is stirred at a stirring speed of 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 17.5 wt% copper powder, 0.6 wt% nickel powder, 0.3 wt% rare earth metal powder, 1.5 wt% titanium carbide whiskers, and the remainder being molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain a heat-resistant and tensile molybdenum-copper alloy material.
[0038] Comparative Example 6: Comparative Example 6 is based on Example 1, with the following adjustment: no dispersion pretreatment of titanium carbide whiskers is performed, while other processes remain unchanged. Specifically: A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material includes the following steps: S1: Molybdenum powder, copper powder, nickel powder, and cerium powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers are added and the mixture is stirred at 50 r / min for 45 minutes to obtain an alloy mixture. The alloy mixture comprises the following raw material components by mass percentage: 17.5 wt% copper powder, 0.6 wt% nickel powder, 0.3 wt% rare earth metal powder, 1.5 wt% titanium carbide whiskers, and the remainder being molybdenum powder; S2: The alloy mixture is first vacuum dried at 80℃ for 3 hours; then placed in a mold and cold isostatically pressed at 200MPa for 20 minutes; next, it is sintered at 1100℃ for 20 minutes under argon protection using an electric discharge plasma sintering machine; after sintering, it is allowed to cool naturally to room temperature, then heated to 700℃ and held for 2 hours under argon protection, and then furnace cooled to room temperature; finally, it is rolled at 950℃ at a rolling speed of 0.8m / s until the total deformation is 65%, to obtain the molybdenum-copper alloy material. S3: Laser cladding, nitriding: S31: Molybdenum powder, titanium powder, chromium powder, nickel powder, and tungsten powder are added to a ball mill. Argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as grinding balls. The mixture is ball-milled for 8 hours at a ball-to-material ratio of 10:1 and a ball milling speed of 300 r / min. Then, titanium carbide whiskers are added and the mixture is stirred at 50 r / min for 45 minutes to obtain the cladding material. The cladding material comprises the following raw material components by mass percentage: 2 wt% titanium powder, 12.5 wt% chromium powder, 3 wt% nickel powder, 2.5 wt% titanium carbide whiskers, 3.5 wt% tungsten powder, 0.3 wt% rare earth metal powder, and the remainder is molybdenum powder; S32: Laser cladding is performed on the surface of molybdenum-copper alloy material using cladding material to obtain a cladding layer; the parameters of laser cladding are: argon as protective gas, laser power of 900W, scanning speed of 4mm / s, spot diameter of 3mm, and cladding thickness of 0.8mm. S33: After laser cladding, the cladding layer is finely ground and polished to a roughness of 0.5μm, and then nitrided to obtain a heat-resistant and tensile-strength molybdenum-copper alloy material. The nitriding parameters are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:1.5, a gas flow rate of 0.75L / min, a working voltage of 700V, a nitriding temperature of 550℃, a nitriding pressure of 0.3MPa, and a nitriding depth of 0.15mm.
[0039] Performance testing: The heat-resistant and tensile-strength molybdenum-copper alloy materials prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to tensile property testing and high-temperature resistance testing. The specific testing methods are as follows: (1) Tensile property test: Based on GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test at room temperature" as the reference standard, a universal testing machine was used to test the tensile properties of the heat-resistant and tensile molybdenum-copper alloy material. The tensile rate was 5×10⁻⁶. −4 s -1 ; (2) High temperature resistance test: The heat-resistant and tensile molybdenum-copper alloy material was heated to 500℃ and held for 20 minutes to ensure uniform temperature. Then, it was subjected to a 5×10−4 s -1 The tensile properties were tested at the stretching rate. The specific test results are shown in Table 1 below: Table 1
[0040] Results Analysis: The test results in Table 1 above show that: Comparing Examples 1-3, it can be seen that Example 2 uses the least amount of reinforcing components in the alloy mixture and cladding material, thus exhibiting weaker tensile strength and heat resistance compared to the other two examples. Example 3 uses the most reinforcing components in the alloy mixture and cladding material, resulting in better tensile strength and heat resistance compared to Example 1, although the difference is minimal. Overall, Examples 1-3 of this invention all demonstrate excellent tensile strength and heat resistance. However, considering cost, Example 1 is considered the optimal embodiment of this invention.
[0041] Comparing Example 1 and Comparative Example 1, it can be seen that: in Comparative Example 1, since titanium carbide whiskers were not added to the alloy mixture, the product obtained in Comparative Example 1 did not obtain the whisker's enhancement effect on the tensile properties of the alloy material, which led to a significant decrease in tensile strength.
[0042] Comparing Example 1 and Comparative Example 2, it can be seen that: in Comparative Example 2, since titanium carbide whiskers were not added to the cladding material, the creep resistance and softening resistance of the cladding layer of the product obtained in Comparative Example 2 were reduced, resulting in a significant reduction in its heat resistance.
[0043] Comparing Example 1 and Comparative Examples 3-5, it can be seen that both laser cladding and nitriding are important measures of the present invention to improve the tensile strength and heat resistance of molybdenum-copper alloy materials. Therefore, the performance of the products obtained in Comparative Examples 3-5 is significantly reduced, especially in terms of heat resistance.
[0044] Comparing Example 1 and Comparative Example 6, it can be seen that the dispersion pretreatment of titanium carbide whiskers greatly improves the dispersion uniformity of titanium carbide whiskers, thereby significantly improving the tensile strength of wear-resistant and tensile-resistant molybdenum-copper alloy materials.
[0045] In summary, this invention has yielded a heat-resistant and tensile molybdenum-copper alloy material with high tensile strength and high heat resistance.
[0046] For those skilled in the art, it is obvious that the present invention is not limited to the details disclosed in the exemplary embodiments described above. The present invention can be implemented in other specific ways without departing from its spirit and essential characteristics. Therefore, the foregoing embodiments should be considered exemplary rather than restrictive from any perspective. The scope of protection of the present invention is defined by the appended claims. Therefore, all variations falling within the meaning and scope of the equivalent elements of the claims should be attributed to the scope of the present invention.
Claims
1. A method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material, characterized in that: Includes the following steps: S1: Add molybdenum powder, copper powder, nickel powder, and rare earth metal powder into a ball mill and ball mill; then add titanium carbide whiskers and mix to obtain an alloy mixture. S2: The alloy mixture is dried, cold isostatically pressed, sintered, heat-treated, and rolled to obtain a molybdenum-copper alloy material. S3: Molybdenum-copper alloy material is laser clad and nitrided to obtain heat-resistant and tensile-strength molybdenum-copper alloy material; The alloy mixture comprises the following raw material components by mass percentage: 15-20 wt% copper powder, 0.4-0.8 wt% nickel powder, 0.1-0.5 wt% rare earth metal powder, 1-2 wt% titanium carbide whiskers, and the remainder being molybdenum powder; The laser cladding material comprises the following raw material components by mass percentage: 1-3 wt% titanium powder, 10-15 wt% chromium powder, 2-4 wt% nickel powder, 2-3 wt% titanium carbide whiskers, 2-5 wt% tungsten powder, 0.1-0.5 wt% rare earth metal powder, and the remainder being molybdenum powder.
2. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: Before adding the titanium carbide whiskers, a dispersion pretreatment is performed on them. The specific method is as follows: (1) Add the titanate coupling agent to the ethanol aqueous solution, adjust the pH to 4.8~5.2, stir and mix to obtain the coupling agent hydrolysate; (2) Add the titanium carbide whiskers to the coupling agent hydrolysate, stir and mix, filter, wash and dry; then add to anhydrous ethanol, ultrasonically disperse to complete the dispersion pretreatment. The ratio of the titanate coupling agent and the aqueous ethanol solution is (0.02~0.06)g:1mL; the ratio of the titanium carbide whiskers, the coupling agent hydrolysate, and the anhydrous ethanol is (1~2)g:5mL:5mL.
3. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: The parameters for ball milling are as follows: argon is used as the protective gas, anhydrous ethanol is used as the dispersion medium, and zirconia balls are used as milling balls; the ball-to-material ratio is (5~20):1, the ball milling speed is 200~400 r / min, and the ball milling time is 6~10 h; the mixing is performed by mixing at a stirring speed of 40~60 r / min for 30~60 min.
4. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: The cold isostatic pressing is performed by holding the pressure at 180~220MPa for 10~30min.
5. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: The sintering process is as follows: under argon protection, discharge plasma sintering is performed at 1000~1200℃ for 10~30 minutes.
6. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: The heat treatment is performed by holding the temperature at 600-800℃ for 1-3 hours under argon protection.
7. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: The rolling deformation is as follows: at 900~1000℃, rolling is performed at a rolling speed of 0.2~1m / s until the total deformation is 50~80%.
8. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: The parameters for laser cladding are as follows: argon gas is used as the protective gas, laser power is 800~1000W, scanning speed is 3~5mm / s, spot diameter is 2~4mm, and cladding thickness is 0.5~1mm.
9. The method for preparing a heat-resistant and tensile-strength molybdenum-copper alloy material according to claim 1, characterized in that: The parameters for nitriding are as follows: a mixture of nitrogen and ammonia is used as the nitriding medium, with a volume ratio of 1:(1~2), a gas flow rate of 0.5~1L / min, a working voltage of 600~800V, a nitriding temperature of 500~600℃, a nitriding pressure of 0.2~0.4MPa, and a nitriding depth of 0.1~0.2mm.
10. A heat-resistant and tensile-strength molybdenum-copper alloy material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9.